Kolaborasi antara Sekolah dan Orang Tua dalam Pendidikan Inklusi - Aryuni, Erika; Zalianti, Sonia Firda; Putra, Yendra Pradana; Mustika, Dea (Lembaga Yasin AlSys, 2024)
Parents are responsible for the development and education of their children. Parental involvement determines the success of implementing inclusive education in an educational unit. With the involvement of parents in the implementation of inclusive education, synergy in the implementation of inclusive education runs well. The aim of this research is to describe collaboration between schools and parents in inclusive education. This type of research is qualitative with descriptive methods. Data collection uses observation and documentation techniques through journals and books on the internet. The research results show that the role of parents in implementing inclusive education can be carried out in a participatory and collaborative manner. The positive role of parents can influence the implementation of inclusive education. The results of this research also show that good cooperation between parents and the school, in this case teachers and education staff, is very influential in the process of implementing inclusive education and supports the creation of better and more meaningful inclusive learning.